Pattern recognition receptors in grass carp Ctenopharyngodon idella: I. Organization and expression analysis of TLRs and RLRs. (November 2017) - Liao, Zhiwei; Wan, Quanyuan; Su, Hang; Wu, Changsong; Su, Jianguo
Abstract: Pattern recognition receptors (PRRs) play indispensable roles in the immune responses against invading pathogens. In the present study, we systematically identified and characterized Toll-like receptors (TLRs), retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs) as well as their adaptors in grass carp ( Ctenopharyngodon idella ). A comprehensive analysis of BLAST and other bioinformatics methods showed that C. idella TLR family consist of 21 members and their adaptors contain four members. Phylogenetic analyses confirmed the existence of six TLR subfamilies (TLR1, 3, 4, 5, 7 and 11 subfamily) in C. idella and revealed their homologous relationships with other species. Most C. idella TLRs possess three typical structural features of TLR protein family: LRR, TM and TIR domains. Meanwhile, RLR family consist of three conserved members (RIG-I, MDA5 and LGP2) as well as two adaptors (IPS-1 and STING) in C. idella . mRNA expression analyses of TLRs, RLRs and their adaptors indicated that most members are sustainably expressed in multiple tissues before and after grass carp reovirus (GCRV) or Aeromonas hydrophila infection, while TLR9, TLR20a/b, TLR25, TIRAP, SARM1 and STING are transiently expressed in specific tissues. TLRs are transmembrane receptors with few introns, while RLRs are cytoplasmic receptors with plenty of introns. TLRs and RLRs interact with adaptors to perform their functions via various signaling pathways. In conclusion, this study systematically explores the characteristics of TLRs and RLRs in C. idella and provides evidence for the response patterns after viral and/or bacterial infection in vivo . These results contribute to studying the regulation mechanisms of TLR and RLR signaling pathways, and deeply understanding fish immune responses against pathogen infection. Highlights: Systematically characterized TLRs, RLRs and their adaptors in Ctenopharyngodon idella. Comprehensive phylogenetic analyses of TLRs and RLRs were conducted among various species. Examined mRNA expressions of TLRs, RLRs and their adaptors in RNA-Seq datasets from other researches after challenge. Uncertainty of TLR nomenclature was discussed.